The Effect of the Audiovisual tactile on Sensory Recovery Following Ulnar Nerve Repair - R Hasanzadeh; H Shariatzadeh; AR Roofigari; MR Keihani (Vesnu Publications, 2008)
Introduction: The aim of this study was to determine if deprivation of tactile sense could be compensated by hearing sense, early after the nerve repair in hand. This may hypothetically help to maintain the cortical hand representation during the early denervation period. Materials and Methods: ";Audiovisual tactile"; apparatus was used early after repair of the ulnar nerve in order to improve recovery of hand sensibility by maintaining an active sensory map of the hand in the somatosensory cortex during the differentiations period. This tool was used in a 25-years-old man. Then sensory evaluation was performed at regular intervals in 2, 5 and 7 months after the intervention. Results: Sensory improvement was better in the patient who used the artificial sensibility regimen compared with the others who did not. Conclusion: This study suggests that the onset time of sensory afferent inflow after nerve repair is a very important agent to focus on sensory re-education. Keywords: Nerve repair, sensory re-education, audiovisual tactile apparatus, hand sensibility